Artists as Researchers: A New Paradigm for Art Education in Europe - Hannula, Mika; Kaila, Jan; Palmer, Roger; Sarje, Kimmo (Helsinki Academy of Fine Arts, 2009)
Studio-based artistic research and doctoral degrees for artists are now important aspects of contemporary art and art education. Artists as Researchers presents a selection of essays that address various approaches to research in contemporary art. It contains contributions from more than twenty international artists, art teachers, curators, historians and critics, all of whom participated in the 20102012 EU project Changing Identities and Contexts in the Arts.
Keywords: Artistic research; Education